What Makes Human Resource Professionals Effective? An Exploratory Lesson From Techno-Based Telco Firms of a Developing Country - Fareed, Muhammad; Ahmad, Aqeel; Salleh, Sri Sarah Maznah Mohd; Noor, Wan Shakizah Wan Mohd; Isa, Mohd Faizal Mohd (Frontiers in Psychology, 2022)
Extant research primarily focuses on the driving factors of Human Resource (HR) professionals’ effectiveness in Telco firms of Pakistan. That is due to the need for HR professionals to be effective has risen in the 21st century for gaining sustainable competitive advantage. This research paper examines the level of HR professionals’ effectiveness in Telco firms of Pakistan and explores the strategic functions and their elements owing to which HR professionals can be effective in fulfilling their tasks and duties. Ten HR executives from five Telco firms were interviewed. The study finds nine key strategic functions along with their forty elements which indicate the effectiveness of HR professionals. Successful implementation of these strategic functions and their elements offers Telco firms to sustain competitive advantage. Hence, it extends the resource based-view (RBV) theory by accumulating the additional determinants in the context of Pakistan. The research provides the insights for policy makers and practitioners which explain the key strategic functions and substantial variables through which HR professionals can augment their effectiveness in sustaining competitive advantage.